Usability Evaluation of a Smartphone Medication Reminder Application in Patients Treated With Short-term Antibiotic. Issue 10 (October 2021) - Sherwin, LeeAnne B.; Deroche, Chelsea B.; Yevu-Johnson, Justina; Matteson-Kome, Michelle; Bechtold, Mathew; Jahnke, Isa; Alexander, Gregory L.
Abstract : Medication adherence is poor in persons with chronic disease, especially in those with multiple chronic diseases, one of which is a psychological disorder. Social support, medication education, and external reminders have been identified as facilitators of adherence. Mobile health applications have the potential to enhance adherence; however, it is unknown if publicly available applications are user-friendly and useful. We aimed to examine the usability and feasibility of the "MediSafe" medication reminder application in adults with diarrhea-predominant irritable bowel syndrome undergoing short-term antibiotic therapy and a "Medfriend" from their social support network (N = 14). A mixed-methods study was conducted. All patient participants used the MediSafe application daily for 14 days. Ease of use, ease of learning, and satisfaction scales were rated highest by both patient participants and Medfriends, whereas usefulness was rated lowest by both groups, with Medfriends' usefulness rating significantly lower than that of patient participants. Telephone interviews identified patient participants found the application instrumental in facilitating medication adherence, and Medfriends viewed themselves as active participants in the patient participants' care. The MediSafe medication reminder application is easy to use and accepted by both patients and their designated Medfriend. The MediSafe is instrumental in facilitating short-term antibiotic adherence and social support engagement.